Feedback Enhances Preschoolers’ Performance in an Inhibitory Control Task - Oeri, Niamh; Buttelmann, David; Voelke, Annik E.; Roebers, Claudia M. (Frontiers in Psychology, 2019)
Accomplishing inhibition tasks requires not only inhibitory skills but also goal maintenance. The present study aimed to disentangle goal maintenance from inhibition. Therefore, we experimentally manipulated goal-maintenance demands by means of feedback. Three-year-old (n = 84) and 4-year-old (n = 75) preschoolers’ were randomly assigned to one of four experimental conditions. Results revealed an age-dependent pattern: three-year-olds that were assigned to one of the conditions with feedback outperformed those assigned to the control condition without feedback. It seems that especially performance-related feedback reduced goal-maintenance demands in 3-year-olds, resulting in enhanced inhibitory performance. Four-year-olds, in contrast, showed high performance across all conditions. Age-differences between the 3- and 4-year olds were only significant for the control condition. Thus, with feedback, performance of the 3-year-olds was similar to that of the 4-year-olds. The present results seem to indicate that in an inhibition task, 3-year-olds’ struggle not only with inhibiting a prepotent response but also with adhering to the task goal.